Pengembangan Keterampilan Berkelanjutan di Pakistan: Menjembatani Kesenjangan dalam Kebijakan Pendidikan Kejuruan dan Teknik – Tinjauan Literatur Sistematis - Wazir Ali; Abdul Rahman; Ravik Karsidi (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2024)
Skill development is pivotal to Pakistan’s economic and social transformation, addressing human capital challenges. This systematic literature review synthesizes findings from 38 peer-reviewed studies conducted between 2015 and 2024 to evaluate Pakistan’s existing policies and practices. Findings reveal myriad barriers in Pakistan’s vocational education ecosystem, including outdated curricula, weak industry-academia collaboration, and governance inefficiencies, disproportionately affecting vulnerable rural populations. Programs like the National Skills Strategy (NSS) and Punjab Skills Development Fund (PSDF) aim to align education with labor market demands, but financial constraints and governance inefficiencies hinder implementation. Due to infrastructural inadequacies, digital literacy and entrepreneurial education programs face implementation challenges. The study advocates for experiential learning modalities and inclusive policies to dismantle socio-cultural barriers. Comparisons with global models such as Germany’s dual education system and Singapore’s SkillsFuture initiative illustrate opportunities to modernize Pakistan’s TVET (Technical and Vocational Education and Training) framework. Policy recommendations emphasize the need for strategic investments in digital infrastructure to modernize curricula, foster industry partnerships, and integrate cutting-edge technologies aligning TVET with Industry 4.0, fostering public-private partnerships, and promoting gender-inclusive strategies to enhance workforce readiness and economic competitiveness. These reforms align with Sustainable Development Goals (SDGs) 4 and 8, offering a pathway for Pakistan to enhance workforce readiness, foster economic competitiveness, and promote equitable socioeconomic development.